“Lock and Protect”: Development of a Digital Decision Aid to Support Lethal Means Counseling in Parents of Suicidal Youth - Asarnow, Joan R.; Zullo, Lucas; Ernestus, Stephanie M.; Venables, Chase W.; Goldston, David B.; Tunno, Angela M.; Betz, Marian E. (Frontiers in Psychiatry, 2021)
Objective: Reducing access to lethal methods is an effective suicide prevention strategy that is often neglected in routine care. Digital interventions have shown promise for addressing such gaps in care; and decision aids have proven useful for supporting complicated health-related decisions, like those involving lethal means restriction. This article describes a parent/caregiver-facing web-based decision aid, the development process, and user testing. Method: A user-centered, participatory, mixed methods development design was employed. Beginning with an adult-focused decision aid developed by members of our team, we assessed ten iterations of the parent/caregiver decision aid with stakeholders (N = 85) using qualitative interviews and quantitative surveys. Stakeholders included: parents/caregivers whose children had histories of suicidal episodes before age 25, young adults with histories of suicidal thoughts/behaviors, firearm owners/representatives from firearm stores/ranges/groups, mental and medical health care providers, and emergency responders. Results: The final “Lock and Protect” decision aid was viewed as “useful for changing access to lethal means” by 100% of participants. Ninety-four percent of participants rated the information on reducing access to lethal means as good to excellent, and 91% rated the information on storage options as good to excellent. Qualitative feedback underscored a preference for offering this digital tool with a “human touch,” as part of safety and discharge planning. Conclusions: “Lock and Protect” is a user-friendly web-based tool with potential for improving rates of lethal means counseling for parents/caregivers of suicidal youth and ultimately reducing pre-mature deaths by suicide.